Inhibition of α‐glucosidase activity by N‐deoxynojirimycin analogs in several insect phloem sap feeders. (18th August 2015) - Ya'kobovitz, Marina Katzman; Butters, Terry D.; Cohen, Ephraim
Abstract: Secondary metabolites and synthetic iminosugars that structurally resemble monosaccharides are potent inhibitors of α‐glucosidase activity. The enzyme is core in cleaving sucrose in phloem feeding insects and it also plays a crucial role of reducing osmotic stress via the formation of oligosaccharides. Inhibition of hydrolysis by iminosugars should result in nutritional deficiencies and/or disruption of normal osmoregulation. Deoxynojirimycin (DNJ) and 2 N‐alkylated analogs [N‐butyl DNJ (NB‐DNJ) and N‐nonyl DNJ (NN‐DNJ)] were the major iminosugars used throughout the study. The extensive experiments conducted with α‐glucosidase of the whitefly Bemisia tabaci indicated the competitive nature of inhibition and that the hydrophilic DNJ is a potent inhibitor in comparison to the more hydrophobic NB‐DNJ and NN‐DNJ compounds. The same inhibitory pattern was observed with the psyllid Cacopsylla bidens α‐glucosidase. In contrast to the above pattern, enzymes of the aphids, Myzus persicae and Aphis gossypii were more sensitive to the hydrophobic iminosugars as compared to DNJ. In vivo experiments in which adult B. tabaci were fed dietary iminosugars, show that the hydrophilic DNJ was far less toxic than the lipophilic NB‐DNJ and NN‐DNJ. It is proposed that this pattern is attributed to the better accessibility of the hydrophobic NN‐DNJ to the α‐glucosidase membrane‐bound compartment in the midgut. Based on the inhibitory effects of certain polyhydroxy N‐alkylated iminosugars, α‐glucosidase of phloem feeding hemipterans could serve as an attractive target site for developing novel pest control agents.